(untitled) (Bangladesh Pharmaceutical Journal, 2015)
Brassica rapa subsp. chinensis (L.) Hanelt is a popular herb in Bangladesh. In the present studies, the plant has been assessed to evaluate its in vitro thrombolytic and membrane stabilizing properties. Initially, the plant was collected, processed and extracted with methanol and the concentrated crude methanol extract was fractionated into petroleum ether, carbon tetrachloride, chloroform and aqueous soluble materials. All extractives, including the parent extract were subjected to thrombolytic and membrane stabilizing bioassays. In case of thrombolytic study, the carbon tetrachloride soluble fraction exhibited highest clot lysis. Here, streptokinase and distilled water were used as positive and negative control, respectively. However, in the assay for membrane stabilizing activity, the crude methanol extract along with other extractives were capable to inhibit hemolysis of erythrocyte membrane in hypotonic solution- and heat- induced conditions, which indicated anti-inflammatory property of the samples. Acetyl salicylic acid was used as standard drug in this assay. This represents the first report of thrombolytic and membrane stabilizing activities of B. rapa subsp. chinensis. DOI: http://dx.doi.org/10.3329/bpj.v17i2.22336 Bangladesh Pharmaceutical Journal 17(2): 172-176, 2014